Involvement of shedding induced by ADAM17 on the nitric oxide pathway in hypertension - da Silva, Mirelly Cunha; dos Santos, Vanessa Maria; da Silva, Matheus Vinícius B.; Prazeres, Tereza Cristina M. M.; Cartágenes, Maria do Socorro S.; Calzerra, Natália Tabosa M.; de Queiroz, Thyago Moreira (Frontiers in Molecular Biosciences, 2022)
A Disintegrin and Metalloprotease 17 (ADAM17), also called tumor necrosis factor-ɑ (TNF-ɑ) convertase (TACE), is a well-known protease involved in the sheddase of growth factors, chemokines and cytokines. ADAM17 is also enrolled in hypertension, especially by shedding of angiotensin converting enzyme type 2 (ACE2) leading to impairment of angiotensin 1-7 (Ang-(1-7)) production and injury in vasodilation, induction of renal damage and cardiac hypertrophy. Activation of Mas receptor (MasR) by binding of Ang-(1-7) induces an increase in the nitric oxide (NO) gaseous molecule, which is an essential regulator of vascular function and blood pressure (BP) control. On the other hand, TNF-ɑ has demonstrated to induce a decrease in NO bioavailability, triggering a disrupt in endothelium-dependent vasorelaxation. In spite of the previous studies, little knowledge is available about the involvement of the metalloprotease 17 and the NO pathways. Here we will provide an overview of the role of ADAM17 and Its mechanisms implicated with the NO formation.